Comparative analysis of AR variant AR-V567es mRNA detection systems reveals eminent variability and questions the role as a clinical biomarker in prostate cancer - Bernemann, Christof; Humberg, Verena; Thielen, Barbara; Steinestel, Julie; Chen, Xin; Duensing, Stefan; Schrader, Andres J.; Boegemann, Martin (Clinical cancer research, 2019)
Purpose: Androgen receptor splice variants are known to facilitate resistance of prostate cancer cells toward antihormonal therapies. However, detection of the most prominent variant, AR-V7, on its own, is not sufficiently accurate for prediction of response. Thus, simultaneous detection of other variants might improve prediction. AR-V567es has been shown to be expressed in late stages of prostate cancer. Yet, there have been discrepant results regarding incidence of AR-V567es. We therefore aimed to perform a comprehensive comparison of different detection approaches for AR-V567es mRNA. Experimental Design: We compared a custom-made, probe-based PCR assay with 6 published AR-V567es detection PCR assays in distinct samples, that is, cancer cell lines, LuCaP xenografts, primary and metastatic tumor samples, and circulating tumor cells (CTC). Results: Using distinct approaches, we concordantly detected expression of AR-V567es in only three of 45 samples (LuCaP xenografts 86.2 and 136s2 as well as one CTC sample). We observed varying results in all other samples. Specificity analysis displayed nonspecific binding of 5 previously published PCR assays to AR full-length mRNA in the absence of AR-V567es. Conclusions: Validation of biomarker detection approaches is one of the most critical steps before transfer into clinical application. By performing comparative analysis of different detection approaches, we revealed eminent variability among previously described systems. Furthermore, we demonstrate an overestimation of AR-V567es in prostate cancer, presumably due to nonspecific detection of AR-FL mRNA. Therefore, any correlation between AR-V567es expression and clinical responses is highly doubtful and does not reflect the biological nature of the disease.
Online veröffentlicht: 16. April 2019
Gesehen am 06.08.2019